Local Business Taxation and Competition for Capital: The Choice of the Tax Rate - Thiess Buettner (Center for Economic Studies and ifo Institute (CESifo), 2001)
A theoretical model describes the local choice of the tax rate on capital income. It establishes preferences and various fiscal conditions - including the tax rates of competing jurisdictions - as determinants of the tax rate. The empirical implications are tested using a large panel of jurisdictions in Germany, which have discretion in setting the local rate of the business tax. Tax competition is identified by means of instrumental variables techniques. Despite significant competition effects between local neighbors, where tax rates are strategic complements, jurisdictions are found to have some leeway in using the tax rate as an instrument of their policy. In particular, large jurisdictions set higher tax rates in interjurisdictional competition.
Keywords: 330; Local public finance; tax competition; instrumental variables; spatial econometrics; business taxation